Are they sisters? Using text mining approach to understand perceptions about Madeira and Bermuda - Bilro, R.G.; Loureiro, S. M. C.; Ferro, T. M. (48th annual European Marketing Academy annual conference - EMAC, 2019)
The current study explores how tourists perceive two islands with identical culture, but different demographic characteristics. Two complementary methodologies are employed: Netnography and Text Mining. Eight encodings are used based on the literature: Rating, Categories, Membership Level of reviewers, Language type, Tourism Experience Model, Content, and Symbology and Positive/Negative information. With the first methodology, all encodings are analyzed, while in the Text Mining, only three: TEM, ML and categories. Customer satisfaction is slightly superior in Madeira. Lifestyle and Leisure and Tourism, Travel and Commuting are the main themes. Reviewers are engaged with the destinations and the re-purchase scenario is highly probable.